'Make Us More Useful to Society!': The Scandinavian Design Students' Organization (SDO) and Socially Responsible Design, 1967–1973. (1st September 2016) - Lie, Ida Kamilla
Abstract: This article explores the brief but ardent history of the Scandinavian Design Students' Organization (SDO) in the late 1960s. Dissatisfied with contemporary design practice and education, a group of students aimed to reposition design, both in its methods and purpose, bringing it more in line with what they perceived to be the urgent challenges of society. The article focuses on the three summer seminars organized by the SDO as well as the two published issues of the members' magazine &, and places them in a broader history of social design, co-design, and participatory design. The study also reveals the mutual influence between Nordic design students and Victor J. Papanek, and places this co-operation in a broader geographic context.